IMPLEMENTATION OF AN EFFECTIVE EDUCATIONAL MANAGEMENT SYSTEM IN IMPROVING THE QUALITY OF EDUCATIONAL SERVICES IN ISLAMIC BOARDING SCHOOL - Mannan, Ahmad Faidul; Jannah, Ulfa Qomariatul; baharun, hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyze the implementation of an adequate education management system to improve the quality of educational services at Nurul Jadid Islamic Boarding School by emphasizing skills relevant to the future. This study also explores the application of CCTES (Controversy, Change, Trend, Emergency, Solution) in managing Islamic boarding school education that can prepare students to face global challenges. Using a qualitative approach with a case study design, this study involved interviews, observations, and documentation as data collection methods. The primary informants in this study consisted of foster parents, Islamic boarding school administrators, students, teachers and educational staff. The results of the study indicate that the application of technology in the form of interactive textbooks based on gamification contributes to reducing students' anxiety about learning that is considered problematic. In addition, an effective management system that integrates professional skills and technology in learning also improves the quality of education and skills relevant to future needs. The implications of this study indicate that applying an innovative managerial approach in Islamic boarding schools can improve the quality of teaching and the readiness of students to face technological developments and future challenges. This research also contributes to updating the perspective on educational management in Islamic boarding schools, by including technology and professional skills as essential components in the education system.